The impact of Hurricane Maria on Puerto Rico’s health system: post-disaster perceptions and experiences of health care providers and administrators - Sheilla L. Rodríguez-Madera (BMC, 2021)
Abstract Background After its landfall in Puerto Rico in 2017, Hurricane Maria caused the longest blackout in United States history, producing cascading effects on a health care system that had already been weakened by decades of public sector austerity and neoliberal health reforms. This article addresses how health care professionals and administrators experienced the health care system’s collapse and the strategies used by them to meet their communities' health needs. Methods Data were collected between September 2018 and February 2020. Ethnographic observations in health care facilities and semi-structured qualitative interviews with representatives of the health care system were conducted. This paper focuses on data from interviews with health care providers (n = 10) and administrators (n = 10), and an ethnographic visit to a pop-up community clinic. The analysis consisted of systematic thematic coding of the interview transcripts and ethnographic field notes. Results Results provide insight on how participants, who witnessed first-hand the collapse of Puerto Rico’s health care system, responded to the crisis after Maria. The prolonged power outage and lack of a disaster management plan were partly responsible for the death of 3,052 individuals who experienced extended interruptions in access to medical care. Participants reported a sense of abandonment by the government and feelings of mistrust. They also described the health sector as chaotic and lacking clear guidelines on how to provide services or cope with personal crises while working under extreme conditions. In such circumstances, they developed resilient responses to meet communities’ health needs (e.g., itinerant acupuncture services, re-locating physicians to local pharmacies). Conclusions Participants’ narratives emphasize that the management of Hurricane Maria was fraught with political and economic constraints affecting Puerto Rico. Ineffective planning and post-Maria responses of the local and federal governments were determinants of the disaster’s impact. The findings contribute to a growing scientific literature indicating that Hurricane Maria revealed ‘the collapse before the collapse,’ alluding to the structural deficiencies that presaged the catastrophic event. In the context of governmental abandonment, the authors argue for the importance of developing alternative strategies in post-disaster health care provision among health professionals and administrators who work at the front lines of recovery.